SUCCESS AND FAILURE ALONG THE MODDER RIVER DURING THE ANGLO-BOER WAR: THE INFLUENCE OF TERRAIN - Smit, H A. P.; Janse van Rensburg, H. S. (Scientia Militaria - South African Journal of Military Studies, 2014)
The influence of terrain[i] on military operations is a well-known and well-researched topic. In a South African context, the body of literature about this topic is, however, not as well developed. This article strives to make a contribution to literature about South African battles and the influence of terrain on the outcome of such battles. During the Anglo Boer War (1899–1902), two important battles were fought along the Modder River. The first of these battles is known as the Battle of Modder River or Twee Riviere (Two Rivers, if directly translated from Afrikaans), while the other is known as the Battle of Paardeberg.[ii] These battles were fought in close proximity to one another, both in distance and time. The terrain of the battlefields played a key role in both engagements. This article suggests that the spatial arrangement of the koppies (hills) and the fact that they were much closer to the Boer laager at Paardeberg than at the battle of Modder River played a key role in Cronje’s surrender to the British. [i] During the research for this article, inconsistencies in the use of the concepts ‘terrain’ and ‘topography’ were discovered. According to various geographical and geomorphological definitions, the term ‘topography’ refers to the surface features of an area and includes landforms, as well as other aspects, both of natural and human origin. (Monkhouse, FJ & Small, J (eds). A dictionary of the natural environment. London: Edward Arnold, 1978, 297–298; Monkhouse, FJ, Steyn, JN & Boshoff, LP (eds). A dictionary of geography: Southern African edition. Pretoria: De Jager HAUM, 1993, 337; Small, J & Witherick, M (eds). A modern dictionary of geography. London: Edward Arnold, 1995, 245). ‘Terrain’, on the other hand, is defined as “[t]he physical character of an area, its configuration” (Monkhouse & Small op. cit., p. 292; Monkhouse et al. op. cit., p. 331). However, when they refer to ‘terrain analysis’, Galgano and Palka define it as “the collection, interpretation, and geographic analysis of the natural and man-made features of an area to predict the effect of the terrain on military operations” (Galgano, FA & Palka, EJ (eds). Modern military geography. New York: Routledge, 2011, 415.) For clarity’s sake, in this paper the term ‘terrain’ was taken to mean the natural and man-made features of the area under discussion. [ii] Some authors also use a different spelling, namely Perdeberg.